Ответы и объяснения

Лучший Ответ!
2014-04-14T00:15:16+04:00
А) 1)(ab+b²)²=a²b²+2ab³+b^4
    2)(a-b)²=a²-2ab+b²
    3)(a²-ab)²=a^4-2a³b+a²b²
    4) a²b²+2ab³+b^4    b²(a²+2ab+b²)    
        -------------------- = -------------------- = a²+2ab+b²
                b²                      b²
    5) a^4-2a³b+a²b²     a²(a²-2ab+b²)
       -------------------- = -------------------- = a²-2ab+b²
               a²                      a²
    6) a²+2ab+b²+a²-2ab+b²-(a²-2ab+b²) = 2a²+2b²-a²+2ab-b² = a²+2ab+b² = (a+b)²

При a=-2; b=-3,5  (a+b)²=(-2-3,5)²=(-5,5)²=30,25

б) ( a-1        a+1 )    ( 1        a       1   )    ( (a-1)² - (a+1)² ) * (2a-a²-1)
    (-------  -  --------) * (-----  -  -----  - ----- ) = -------------------------------------- = 
    ( a+1)      a-1  )    (  2       4       4a )             (a²-1)        *      4a

    (a²-2a+1-a²-2a-1)(-a²+2a-1)    -4a(-a²+2a-1)    4a(a²-2a+1)       (a-1)²         a-1
    -------------------------------------- = ------------------ = ----------------- = -------------- = --------
              4a(a²-1)                         4a(a²-1)          4a(a²-1)        (a-1)(a+1)     a+1

При a=-3,75 :

-3,75-1     -4,75     19        8
----------- = -------- = ---- = 1 ----
-3,75+1    -2,75     11       11